On nearly C-compact space - Gopal Adak (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In this paper we have introduced a new type of convex topological space [5] called nearly C-compact space where a convex topological space is a topological space with a convexity [16]. Some fundamental characterizations and various basic properties have been obtained. Its relationship with other types of compact spaces is also investigated